Requirements of Followers on their Leaders’ Competences: - - Ramesberger, Reinhold; Valentin, Bucik (Journal of Positive Management, 2025)
Purpose. Considering the scientific leadership knowledge, makes it obvious that this knowledge is based on top-down approaches. In contrary, the purpose of this study is to examine the bottom-up perspective of followers concerning their competence requirements on their leaders within difficult contexts. Design/methodology/approach. The study comprised the profession field of military, sports and economy. Within this profession groups leader-follower processes are of special importance and, therefore, it was assumed that there will be clearly detectable bottom-up requirements. Competitive athletes (N = 171) from the regional level up to the national team level, workers from different branches (N = 195) and soldiers of combat forces (N = 376) rated within a questionnaire their own requirements on their leaders’ behaviours and competences. The gathered data is analysed using SPSS 28 and AMOS 28. Findings. The results revealed moderate correlations between certain leadership competences and the followers´ engagement. They indicated that the “Knowing-Being-Doing” of leaders is highly relevant for their acceptance by the followers. „Being“ revealed to be the most decisive factor across all three profession groups. In difficult situations, the followers across the surveyed profession groups expect a leader able to take action, give orientation (vision) and to orchestrate a suitable team. Implications. The practical implications for competence development of leaders are: - Successful leadership must be based on the “inside - out principle” - Followers need orientation by a leaders’ vision - In situations outside the comfort zone, followers expect their leaders to take action and make the decisions